Long-term dynamics (1990 to 2004) of the polychaete fauna from the sublittoral soft-bottoms off Punta Coloso (Antofagasta), northern Chile - Carrasco, Franklin D.; Moreno, Rodrigo A. (Scientia Marina, 2006)
Long-term monitoring (1990 to 2004) at four stations (50 to 60 m depth) off Punta Coloso, Antofagasta, northern Chile, has allowed us to study temporal changes in the sublittoral macrobenthic polychaete infauna composition and abundance. The numerical contribution of the polychaete fraction to the total fauna was high (65 to 93%), whereas biomass was smaller and variable (20 to 85%). The number of invertebrate species collected per cruise was relatively low (40 to 90 species) and the number of polychaete species ranged from 18 to 37 per cruise (mean = 29.9), with a cumulative number of 56 polychaete species. The most abundant species collected included the small-sized Aricidea pigmentata Carrasco (26.5%), Magelona phyllisae Jones (22.7%), Paraprionospio pinnata (Ehlers) (13.5%), Tharyx longisetosa Hartmann-Schröder (12.1%), and Prionospio peruana Hartmann-Schröder (11.8%). Clear general patterns or tendencies are not seen in temporal variations of polychaete fauna nor when analyzing the seasons individually. P. pinnata was the only dominant species to show a general tendency in abundance fluctuations. Although the study period included two El Niño events (1991-1992 and 1997-1998), a clear dynamic was not seen in either abundance or dominant species. The analyzed data validate or corroborate high stability or persistence over time that has been suggested for polychaete fauna in the study area. Such stability or persistence exists in spite of high seasonal variability and interannual fluctuations in the region’s oceanographic conditions.